Atrial Fibrillation on Severe Sepsis in Resuscitation - About a Case - Sow O., Barboza D., Manga S.J.,; Diouf E., Gaye I., Diop E.N.,; Bah M.D., Ndoye M.D., Fall M.L., Ba E.B., Traoré M.M., (International Journal of Innovative Research in Medical Science, 2017)
Severe sepsis associated with atrial fibrillation is rare in our practice. It is often responsible for heavy mortality. The immunodepression field (HIV 1) is an often unknown factor of severity that complicates sepsis. We report a case of a 53-year-old patient hospitalized in intensive care for severe sepsis complicated with atrial fibrillation and acute lung edema. Treatment consisted of vascular filling, antibiotic therapy, and Amiodarone. The evolution is marked by a thrombotic accident and an amputation of the foot. However, she has evolved well and was transferred to infectious diseases department on D18.